2011
DOI: 10.33584/rps.15.2011.3197
|View full text |Cite
|
Sign up to set email alerts
|

Can pasture persistence be improved through the use of nonryegrass species?

Abstract: Recent discussion about pasture persistence concentrates on pastures based on perennial ryegrass, the most commonly used grass species. This paper raises the question as to whether some of the causes of poor pasture persistence are due to perennial ryegrass being used in environments to which it is not suited. The adaptation to environmental stresses, particularly water, temperature and nutrient deficiencies, in different regions of New Zealand of tall fescue, cocksfoot, phalaris, and lucerne are discussed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Soil moisture is a limiting factor in the establishment of temperate pastures in New Zealand. This is particularly an issue in a dry autumn when the majority (85%) of pastures are established (Milne 2011); warm, dry soil may inhibit the germination of some species more than others. This will have consequences for pasture composition in the short and longer term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil moisture is a limiting factor in the establishment of temperate pastures in New Zealand. This is particularly an issue in a dry autumn when the majority (85%) of pastures are established (Milne 2011); warm, dry soil may inhibit the germination of some species more than others. This will have consequences for pasture composition in the short and longer term.…”
Section: Introductionmentioning
confidence: 99%
“…Tall fescue has long been promoted as a useful species for many regions of New Zealand (Milne 2011). It is characterised as highly productive in summer, drought tolerant and persistent (Cowan 1956;Cregan 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry clover is a more drought-tolerant perennial Trifolium species than white clover (Dear et al 2003;Milne 2011). During short periods of soil moisture deficit stress (≤54 days), studies under glasshouse and field conditions have shown strawberry clover's superior capacity to maintain leaf production and functionality relative to red and white clovers (Dodd and Orr 1995;Hofmann et al 2007).…”
Section: Drought Tolerancementioning
confidence: 99%
“…Northland and Waikato regions have climates not always conducive for ryegrass to persist without seedling recruitment. Milne (2011) recognised that tall fescue and cocksfoot had higher survival after drought, due to deeper roots (tall fescue), increased root thickness and mass (tall fescue and cocksfoot) and reduced transpiration rate (tall fescue). So, it is not surprising that tall fescue and cocksfoot persist better than perennial ryegrass in our farm system.…”
Section: Introductionmentioning
confidence: 99%